Gambaran Pengetahuan Ablasio Retina pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Kristen Krida Wacana - Anugrahsari, Santi; Lethulur, Shindie Dona Kezia; Sopian, Silvester Rionoviyanus Temiang; Kainama, Chrisella Michelle; Br Tobing, Naomi Regina P (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Retinal detachment is the visual nerve layer in the eyeball from the lower layer or retinal layer of pigment epithelium with accumulation in subretinal fluid. The clinical manifestation of retinal detachment is that the patient's vision can decrease from mild to severe. The symptom that suf erers often complain about is floaters, which are visible objects floating around. Purpose: The research is to determine the knowledge of retinal detachment among medical students at the Faculty of Medicine and Health Sciences, Krida Wacana Christian University. Methods: The design of this research is cross-sectional. Participants completed the questionnaire via Google form from 7 December 2022 to 15 December 2022. This research used random sampling; sample selection was carried out randomly. Participants numbered 108 students. Results: Students who had a high level of knowledge 69 respondents (63.9%), followed by a low level of knowledge, namely 22 respondents (20.4%), and then for a medium level of knowledge there were 17 respondents (15.7%). Conclusion: Most students at the Faculty of Medicine and Health Sciences, Krida Wacana Christian University have a high level of knowledge. This study had variations in respondents' knowledge levels because there were pre-clinical and clinical clerkship students